Prevention of Information Attacks Using Information Technologies is the Main Factor of Information Security Provision - Mamatkodirovich , Usmanov Elbek (Researchparks Publishing, 2022)
The article discusses the expansion of the use of information and communication technologies in all spheres of society, the growing need for information and the strengthening of information attacks, and the fight against various external influences. without studying their content and essence, it is considered impossible to ensure the information security of people in society and combat various alien ideas